Linguistic Meaning Versus Pragmatic Meaning - Mohammad Awwad (European Scientific Journal, ESJ, 2017)
A critical gap between linguistic specifications and context-relevantinterpretation has existed ever since linguists sought to investigate meaning.As a matter of fact, English language has gained an unprecedentedmomentum over the last decades, and the ultimate aim of English languageteaching has revolved around fostering the students’ ability to communicateproficiently in English. In this realm, much emphasis was given on thedevelopment of learners’ oral skills; however, those efforts were watereddown on the progression of linguistic competence on the expense ofcommunicative competence. In an attempt to bridge this gap, this studyadopted Grice’s Cooperative Principle (1975) and embodied examples onhow participants breach and neglect maxims upon which the Cooperativeprinciple rests. For this aim, the study was carried on 100 English majorstudents enrolled in the TEFL class at the Lebanese University (fifth branch);the investigation was carried over a period of four months in spring 2015-2016. The results revealed that despite the subjects’ adequate linguisticproficiency in English, EFL learners still fall behind attaining pragmaticcompetence. The study endorses recommendations for EFL learners,teachers, and curriculum designers.